## 1 + tan^2x =

### To solve this equation, we can use the trigonometric identity for the tangent squared:

tan^2(x) = sec^2(x) – 1

Now, let’s substitute this identity into the equation:

1 + tan^2(x) = 1 + (sec^2(x) – 1)

The ‘1’ terms cancel out, leaving us with:

1 + tan^2(x) = sec^2(x)

Therefore, the simplified equation is:

sec^2(x) = 1 + tan^2(x)

In conclusion, 1 + tan^2(x) is equivalent to sec^2(x)

To solve this equation, we can use the trigonometric identity for the tangent squared:

tan^2(x) = sec^2(x) – 1

Now, let’s substitute this identity into the equation:

1 + tan^2(x) = 1 + (sec^2(x) – 1)

The ‘1’ terms cancel out, leaving us with:

1 + tan^2(x) = sec^2(x)

Therefore, the simplified equation is:

sec^2(x) = 1 + tan^2(x)

In conclusion, 1 + tan^2(x) is equivalent to sec^2(x).

##### More Answers:

Understanding the Slope-Intercept Form | What it is and How to Use it in MathSimplifying the Expression 1 + cot^2x Using Trigonometric Identities

Understanding the Pythagorean Identity | The Relationship between Sine and Cosine in Trigonometry

Error 403 The request cannot be completed because you have exceeded your quota. : quotaExceeded